Studies on Nutritive Quality of Fermented Pork Sausages Stored at Ambient Temperature - P., Pantawane; Zende, R.J.; Paturkar, A.M.; Chavhan, D.M.; K., Nagappa (Journal of Meat Science, 2012)
The sausages fermented with Pediococcus pentosaceus and Glucono-delta-Lactone were analyzed for their nutritive quality attributes. Each group of sausages was further divided into four categories depending upon use of type of casings. Thus T1 and T2 category of sausage were prepared using bacterial culture & natural casing and, bacterial culture & synthetic casing, respectively, while T3 & T4 category of fermented pork sausage were prepared using GdL & natural casing, and GdL & synthetic casing, respectively. A total of 196 sausage samples were evaluated on every 15 days interval upto 90 day to study nutritive quality at ambient storage temperature of 32.2-35.10C. The study revealed that moisture content of all fermented sausages showed a constant reduction during the storage period in all the treatments while fat, protein and ash contents were found to be increased with storage period. No significant difference was observed within all the treatments throughout the ambient storage period.